A novel computer task to assess outcome probability bias. (April 2022) - Draheim, Amanda A.; Anderson, Page L.
Abstract: This research describes the development of a novel computer task to assess outcome probability bias for social anxiety - the tendency to make unrealistically high evaluations of the probability of experiencing a negative outcome when anticipating a social encounter - that improves upon existing measures by using images and by assessing the construct at automatic and controlled levels of processing. The first study evaluated the images selected for the task and the extent to which the task elicited automatic responding, and the second study evaluated the task's reliability and validity. Across both studies, 203 college students completed the outcome probability bias computer task, standardized self-report questionnaires of outcome probability bias, outcome cost bias, depression and stress, and safety behaviors, and completed a behavioral avoidance task. The task demonstrated good to excellent internal consistency (α = 0.82 – 0.96) and significant positive correlations with a standardized measure of outcome probability bias ( r  = 0.33 – 0.48). With one exception, all hypotheses regarding the convergent, discriminant, construct, and criterion validity of the task were supported. Pending replication and additional evaluation, the outcome probability bias computer task may advance research on social anxiety disorder and may be adapted for use with other related disorders. Highlights: Outcome probability bias is a theorized mechanism of social anxiety disorder. Current measures may have limited ecological validity. A computer task allows for visual stimuli, enhancing ecological validity. The present task uses social images to measure outcome probability bias. Findings offer preliminary support for the reliability and validity of this task.